Evolución del espectro polínico en muestras de miel y néctar de un colmenar de Tomiño (Pontevedra) - Aira Rodríguez, María Jesús; Jato Rodríguez, Victoria; Seijo Coello, María Carmen (Botanica Complutensis, 1992)
Seuo CoELLo, MC; AíRA RODRÍGUEZ, Mi. & JATO RODRÍGueZ, V. 1992. Polinie spectrum evolution in honey aud nectar samples of an apiary ofTomiño (Pontevedra). Bat Complutensis 17: 87-97 Quantitative and qualitative pollen analisys in sequencial samples of honey and neclar produced in three apiary in Tomiño (Pontevedra), has been made. The colonies have different tendencies of conduct showed in sequencial pollinic spectrurn. The analisys of commercial honey, let lo characterize it like a polifloral honey with an important percentage of Euc-alyptus pollen.
Keywords: Pollen; honey; polifloral; Tomiño; Spain